Ghosts beneath our feet - Wright, Betty Ren (New York : Scholastic Inc., 1984)
During a summer in an abandoned mining town, Katie's relationship with a rebellious stepbrother improves as they probe the past to find out why there seem to be ghosts, literally, beneath their feet.
"An Apple paperback.
680L
71531
Keywords: GHOSTS -- FICTION; Ghost towns -- Fiction; Brothers and sisters -- Fiction